Comparison of different washing solutions and contact times on the quality maintenance and microbial reduction of fresh-cut iceberg lettuce - DAS, BASANTA KUMAR; DAS, JAYASHREE MADHUSMITA; KESAWAT, MAHIPAL SINGH (The Indian Journal of Agricultural Sciences, 2012)
A study was conducted to evaluate the effect of different washing solutions and contact times on the cut-edge browning and microbial quality of fresh-cut iceberg lettuce. Samples were cut into small pieces, washed for 90 sec. and 180 sec. in normal tap water, chlorinated water (100 ml/l,pH 6.5), electrolyzed water (with free chlorine of 100 m1/l, pH 7.2) or ozonated water (3 ml/l). Samples were then, dewatered, packaged in 30 µm polypropylene bags, and stored at 5°C for nine days. Various quality and safety parameters such as gas composition, off-odour, electrical conductivity, cut-edge browning and microbial numbers were evaluated during storage. Results revealed no detectable off odour in all samples during the storage period. However, significant differences in gas composition and electrolyte leakage were marked in samples washed for 180 sec. Samples washed in chlorine for longer contact time showed least cut-edge browning index and lower microbial numbers than other washings initially as well as finally. Hence, concluded that 180 sec. contact time of chlorine washing was better solution to maintain the microbial quality and cut edge browning of fresh-cut iceberg lettuce.